Junior High School Teacher's Ability in Developing Teaching Preparation in Moral Aqeedah Subjects - Hilmi Mizani (STAI Hubbulwathan Duri, 2022)
The ability to develop teaching preparation, in the sense that a teacher is not only at the level of learning planning design, but also in the process and evaluation of learning, for example, being able to design plans, formulate goals, compile, present materials, media, determine basic competencies, strategy, follow up carry on. The problem in this research is how the teacher's ability to develop teaching preparation in MTSn 1 Banjarmasin. The purpose of this research is to determine the teacher's ability to develop teaching preparation in subjects moral aqidah at MTSn 1 Banjarmasin. This type of research is descriptive qualitative research. The population in this study was 1 teacher at MTSn 1 Banjarmasin. The data in this study were collected using observation, interview, and documentation techniques. Furthermore, the collected data were analyzed using the percentage formula. The results of data analysis through observation and interviews can be concluded as follows: The ability of teachers to develop teaching preparation in subjects the moral creed in MTSn 1 Banjarmasin reached 62.82% and was categorized as good because it was located at an interval of 61% -80%.